Rethinking Work and Learning
XXIV, 274 p.
Keywords: This volume brings together an international group of contributors to explore ways in which social sustainability can be integrated into Adult and Vocational Education (AVE) practices. While it is clear that given the rapid change of work, job-specific training for adults is clearly vital the world over, it is argued here that job-specific training needs re-orientation to include life-specific learning as well. This can come about when the learning opportunities to which citizens have access prepare them for participation in work which is economically productive and at the same time engages them in related civic activities which promote environmental and social sustainability. The re-orientation of current AVE systems can be achieved in two ways: by broadening the educational agenda to include elements of environmental science, politics and the arts, and by including more dialogic and collaborative teaching and learning styles.